Analisis Efektivitas dan Kontribusi BPHTB dan PBB-P2 Terhadap PAD Kota Bekasi 2019-2024 - Adinda Zahra Fadila; Tresno Eka Jaya; Septi Nurmalita (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study analyzes the effectiveness and contribution of Land and Building Acquisition Duty (BPHTB) and Rural and Urban Land and Building Tax (PBB-P2) revenues to the Regional Original Revenue (PAD) of Bekasi City for the 2019-2024 period, and formulates optimization strategies through SWOT analysis. The data used are primary data from in-depth interviews with Bapenda officials, notaries/PPAT, taxpayers, and tax consultants, and secondary data on tax revenue targets and realizations. This study uses a descriptive method with a mixed-methods approach, combining effectiveness and contribution ratio analysis with qualitative SWOT analysis. The results show that: (1) BPHTB effectiveness averaged 99 percent (effective), while PBB-P2 effectiveness averaged 81 percent (fairly effective); (2) BPHTB contribution to PAD averaged 20 percent (moderate) and PBB-P2 contribution averaged 18 percent (poor); and (3) recommended strategies include optimizing tax digitalization, updating tax object data, strengthening inter-agency coordination, and improving taxpayer education and service accessibility.